SATIRE IN JAVANESE TRADITIONAL PROVERB - Irfansyah, Zacki; Bahri, Syamsul; Hasibuan, Juli Rachmadhani (Universitas Negeri Medan, 2020)
The study deals with the satire in Javanese traditional proverb. The objectives of the study were to find out the kinds of satire in Javanese traditional proverb and the use of those proverbs. The research method of this study is textual research. The data of this study were taken from fourty Javanese traditional proverbs that have been choosen before. The data of this research were analyzed by using Alviani™s theory. The researcher found there are sixteen proverbs included in irony, fourteen proverbs included in cynicism, nine proverbs included in sarcasm and one proverb included in satire type. The used of satire in Javanese proverb is to express the opinion, advice, purpose or idea in a figurative language to avoid someone gets hurt and hope that someone can be better.Keywords: Javanese, Proverb, Satire